Estrategias de enfermería para disminuir los riesgos en el paciente derivados de la administración de medicamentos (2024)
Objective: Describe nursing strategies to reduce the risks associated with medication administration. Methodology: In this research, a narrative review of the literature was used, following the five phases proposed by Whittemore and Knafl. Results: The nursing area constantly seeks to improve its services by implementing strategies aimed at reducing the risks associated with the administration of medications, such as: health education, comprehensive assessment of the person, medication reconciliation management, applied resilience by nursing and use of technological tools (clinical software). Conclusions: The administration of medications or pharmacotherapy is a crucial task carried out mainly by nursing professionals. They are responsible for ensuring compliance with the treatment plans prescribed by doctors to improve the health of patients. Therefore, it is important to take into account training programs and protocol implementation as health education strategies. Likewise, the comprehensive assessment of the person and the management of medication reconciliation is relevant to identify data that may affect patient safety in the administration of medications. Resilience applied by nursing, whether anticipatory or based on past experiences, improves the skills of the nursing professional at the time of medication administration. And technological tools, specifically information systems, support the drug administration process.